The Impact of Cultural Heritage on Qingdao’s City Marketing - Li, Boyuon; Garamvölgyi, Judit; Rudnák, Ildikó (Journal of Ecohumanism, 2025)
This paper examines the impact of cultural heritage on the marketing of Qingdao city and analyses how rich cultural heritage resources can be explored, protected and used to enhance the city’s image and attractiveness, thereby contributing to the city’s economic and social development. The study highlights that the cultural heritage of Qingdao encompasses historic buildings, industrial heritage, maritime culture and a multicultural background, which collectively serve as unique resources that provide a substantial foundation for the city’s marketing initiatives. The paper discusses the pivotal role of cultural heritage in urban branding, emphasising that the development of its cultural image, the organisation of thematic activities and the advancement of cultural tourism have collectively contributed to the enhancement of Qingdao’s city image and international influence. The empirical section of the study utilised a questionnaire survey (n=360) to ascertain respondents’ perceptions of the advantages and disadvantages of cultural heritage, their personal valuation of cultural heritage, and their inclination to reside, visit, establish a business or pursue academic studies in Qingdao due to its attractive cultural heritage. The findings of this study contribute to the implementation of effective city marketing strategies in Qingdao, with the overarching objective being the attainment of economic benefits and the preservation and promotion of cultural heritage.